Family life education principles and practices for effective outreach - Duncan, Stephen F.; Goddard, H. Wallace; Sage eBooks (Los Angeles, Calif. ; London : SAGE, 2011)
Drawing on the best scholarship and their own years of professional experience, the authors of this thoroughly updated edition begin by discussing the foundations of family life education and encourage readers to develop their own outreach philosophies.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Family life education; Electronic books